ОСОБЛИВОСТІ ПЕРЕКЛАДУ РЕКЛАМНИХ ТЕКСТІВ (СТИЛІСТИЧНИЙ АСПЕКТ) (Zaporizhzhia Historical Review, 2021)
The article deals with stylistic peculiarities of advertisement translation. Translation of advertisement is one of the most complicated problems. The main attention is drawn to the choice of words and language techniques in advertising. The effect of advertisement is achieved due to the use of rhyme, rhythm, association, use of active verbs and imperatives. Very often the translation may be completely different from its original, because the systems of two languages, cultural and ethnic traditions differ very much.